2021
DOI: 10.1016/j.jfma.2020.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Dysosmia and dysgeusia in patients with COVID-19 in northern Taiwan

Abstract: Background/Purpose To investigate the characteristics of dysosmia and dysgeusia among patients diagnosed with coronavirus disease 2019 (COVID-19) in Taiwan. Methods Prospective data collection between January 22, 2020 to May 7, 2020 of nucleic acid confirmed COVID-19 hospitalized patients in northern Taiwan by the Taiwan Centers for Disease Control were analyzed. Results Of 217 patients enrolled, 78 (35.9%) reported dysosmia (n = 73, 33.6%) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 26 publications
0
16
0
4
Order By: Relevance
“…In particular, 30 (19%) studies obtained follow-up data (either with a prospective or retrospective approach) for at least 20 days after OGD onset; only in 5 OGD persisted in less than 10% of patients that originally developed these symptoms 95 , 44 , 96 , 97 , 98 . Of note, among the four studies with the longest follow-up time (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, 30 (19%) studies obtained follow-up data (either with a prospective or retrospective approach) for at least 20 days after OGD onset; only in 5 OGD persisted in less than 10% of patients that originally developed these symptoms 95 , 44 , 96 , 97 , 98 . Of note, among the four studies with the longest follow-up time (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Although among the studies that clinically addressed COVID-19, the most used form of diagnosis was RT-PCR in the detection of viral RNA, the serological analysis also was used in the detection of IgG and IgM antibodies (Amorim Dos Santos et al, 2021;Amorim Dos Santos et al, 2020b;Brandao et al, 2021;Cebeci Kahraman, Ozen, et al, 2020;L. Chen et al, 2020b;Cherif et al, 2020;Cirillo et al, 2021a;Coke et al, 2021a;Cruz Tapia et al, 2020;Eghbali Zarch & Hosseinzadeh, 2021a;Elibol, 2021;Fantozzi et al, 2020;Fernandes Matuck et al, 2020;Fidan et al, 2021;Freni et al, 2020;Gherlone et al, 2021;Halboub et al, 2020;Hockova et al, 2021;Karadas et al, 2020;Kitakawa et al, 2020a;Lechien et al, 2020b;Moreira et al, 2020a;Morteza Mousavi-Hasanzadeh et al, 2020;Nitecki et al, 2021;Ramires et al, 2021;Saniasiaya et al, 2021;Sheng et al, 2021;Sirin & Ozcelik, 2021;Tham et al, 2021). Sputum and saliva analysis, nasal and throat smears were also used (Bao et al, 2020;Cherif et al, 2020;Coke et al, 2021a).…”
Section: Discussionmentioning
confidence: 99%
“…This recommendation varied a lot. Some authors reported the administration of those principal medicines with a large range of other ones (nasal saline irrigation, hydroxychloroquine, chloroquine, diphenhydramine, acetaminophen, Vitamin B, dipyrone, and Fexofenadine) arbitrarily (Coke et al, 2021a;Halboub et al, 2020;Manzalawi et al, 2020;Morteza Mousavi-Hasanzadeh et al, 2020;Sheng et al, 2021;Tanasa et al, 2020). Taking into account that there are many strands in the therapy approach for COVID-19 a wide range of combinations of medicines were already expected to be observed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations